Pelaksanaan Rehabilitasi dan Reintegrasi Anak Korban Serta Anak Saksi Yang Berhadapan Dengan Hukum di Kabupaten Konawe Provinsi Sulawesi Tenggara - Agus Ariadi; Rahmanudin Tomalili (Fakultas Hukum Universitas Islam Batik Surakarta, 2023)
Child protection is all activities to guarantee, fulfill and protect children and their rights so that they can live, grow and develop and participate optimally in accordance with human dignity and status and receive protection from violence and discrimination. That according to what is mandated in the Child Protection Act and specifically stated in the Regulation of the Minister of State for Women's Empowerment and Child Protection of the Republic of Indonesia Number 11 of 2011, the Government of Konawe Regency, Southeast Sulawesi Province is expected to involve all stakeholders and the community in the Consultation process in encouraging all stakeholders to ensure that children and adolescents, especially girls, are involved in the process of Protection, Social Discrimination, Government Policy regarding the right to legal protection in decision-making, planning and implementation. The purpose of this research is to find out the role of the regional government in the rehabilitation and reintegration of child victims, child witnesses who are in conflict with the law in the Konawe district, Southeast Sulawesi Province, to find out the obstacles encountered in implementing the Rehabilitation and Reintegration Process for child victims, child witnesses who dealing with the law in the district. Konawe Province of Southeast Sulawesi, the nature of this research is sociological juridical research, namely studying, apart from examining the provisions of positive law, various symptoms that arise related to the role of the local government in the rehabilitation and reintegration of child victims, witnesses who are in conflict with the law in Konawe Regency, Southeast Sulawesi Province. The results obtained show that the role of the local government, especially the District Social Service. Konawe in terms of handling child victims who are in conflict with the law including victims of sexual violence, abuse, domestic violence, narcotics abuse and so on, the role of the Kab. Konawe helped accompany and issued a recommendation letter addressed to the head of the District Hospital. Konawe in the service of requesting a Visum Et Revertum examination as a form of waiver of hospital administration fees if there are children who become victims who need examination from the hospital, Rehabilitation Handlers, especially women and children in the district. Konawe There needs to be integrated collaboration with relevant agencies according to the mandate of the Juvenile Criminal Justice System law, both between parents of victims or perpetrators, community leaders, government, educators, families in participating in efforts to protect women and children in Konawe district where especially Konawe Regency has a culture (Culture) / or customs in the life of its people, if there is a report received from the District Social Service. Konawe is in nature to provide assistance to the Victims. Keywords: Local government, Rehabilitation, Child Victims